GC-MS Analysis, HPTLC Fingerprint Profile and Antidiabetic Activity of Methanolic Extract of Perilla frutescens Leaves - Kumar Dixit, Arunesh; Singh, Ajay; Farooq, S.; Kumar Dixit, Umesh; Mehmood, Zafar (Asian Journal of Chemistry, 2022)
The present study was aimed to investigate the phytochemical constituents of the different extracts of Perilla frutescens leaves and identification of the compounds by subjecting it to HPTLC and GC-MS analysis along with antidiabetic property of leaves of P. frutescens. The results from HPTLC finger print scanned at wavelength 200 nm for methanolic extract of P. frutescens leaf revealed the presence of seventeen polyvalent phytoconstituents. The HPTLC finger print scanned at wavelength 200 nm for ethanolic extract of P. frutescens leaves showed fifteen polyvalent phytoconstituents and corresponding ascending order of Rf values ranged from 0.02 to 0.78 in which highest concentration of the phytoconstituents was found to be 13.45 % and its corresponding Rf value was found to be 0.64. α-Amylase inhibition of methanolic extract of P. frutescens leaves was also performed. The standard (acarbose 0.5-2.0 mg/mL) revealed greatest α-amylase inhibitory action from 43.82 ± 0.12 to 88.14 ± 0.32% with IC50 value worth of 0.575 mg/mL. At a similar focus methanol concentrates of P. frutescens leaves showed the inhibitory action from 28.21 ± 0.11% to 68.01 ± 0.11%, with an IC50 worth of 1.15 mg/mL. The methanolic extract of P. frutescens leaves exhibited inhibition of α-amylase enzyme proved the antidiabetic potentiality of P. frutescens leaves.